2009
DOI: 10.1590/s1679-62252009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on the spatial and temporal distribution of the puffer fish Sphoeroides greeleyi and Sphoeroides testudineus in a Brazilian subtropical estuary

Abstract: The spatial and temporal distribution of Sphoeroides greeleyi and Sphoeroides testudineus were established from collections (biological material and environmental data) conducted on a monthly basis from May 2000 to April 2001 in intertidal areas along the north-south axis of the estuarine complex of Paranaguá, Paraná State. In addition to characterizing a north-south spatial gradient, which fluctuates seasonally, the variation in the abiotic factors made possible the division of the estuary into three regions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The higher abundances of juvenile S. testudineus were recorded in the upper estuary (Tidal Creek 3) suggesting the recruitment period was during the dry season, and this period was reported in a subtropical area during the summer period (Fávaro et al ., 2009), coinciding with higher salinity and temperature. However, the adults were recorded in the lower estuary (Mudflat and Creek 1) during the rainy season, when the biomass of the fishes was already higher.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The higher abundances of juvenile S. testudineus were recorded in the upper estuary (Tidal Creek 3) suggesting the recruitment period was during the dry season, and this period was reported in a subtropical area during the summer period (Fávaro et al ., 2009), coinciding with higher salinity and temperature. However, the adults were recorded in the lower estuary (Mudflat and Creek 1) during the rainy season, when the biomass of the fishes was already higher.…”
Section: Discussionmentioning
confidence: 94%
“…Giarrizzo et al (2010) suggested this species displayed tidal migratory behaviour in tropical estuaries during ebb tide, and such behaviour may have influenced our results, because all sampling was carried out at low tide. Furthermore, biotic interactions may have played important implications for distributions of species, since closely related estuarine species often exhibit differences in size or behaviour that may reduce competition and allow coexistence (Fávaro et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, these species may be more adapted to the consistent conditions observed in the north-south axis, or greater availability of suitable habitat (shallow water with adjacent mangroves). Other studies have demonstrated a preference by tetraodontids for such areas (Rocha et al 2002;Schultz et al 2002;Fávaro et al 2009;Pichler et al 2015).…”
Section: Spatiotemporal Variations In Abundancesmentioning
confidence: 86%
“…Diferentemente, S. greeleyi foi pouco abundante no estágio 1, com maiores capturas deste estágio no outono. Juvenis de S. testudineus foram também abundantes em áreas rasas da Baía de Paranaguá, com predominância de juvenis sobre adultos durante quase todo ano, e com juvenis de S. greeleyi em maior núme-ro no verão e no outono (Fávaro et al, 2009). Entretanto, o método amostral utilizado por Fávaro et al (2009) pode ter subamostrado os adultos, que possuem maior capacidade de fuga da rede de arrasto utilizada (Halliday e Young, 1996;Suda et al, 2002).…”
Section: Discussionunclassified